Association between parental absence during childhood and depressive symptoms in adulthood in rural Vietnam - Inoue, Yosuke; Fukunaga, Ami; Stickley, Andrew; Yazawa, Aki; Pham, Thuy Thi Phuong; Nguyen, Chau Que; Hoang, Dong Van; Shrestha, Rachana Manandhar; Phan, Danh Cong; Hachiya, Masahiko; Huynh, Dong Van; Le, Huy Xuan; et al. (Journal of affective disorders, 2022)
While parental absence during childhood has been linked to depression/depressive symptoms in adulthood, no research has been conducted on this association in Vietnam, where many children were separated from their parents during and after the Vietnam War (1955–1975). We examined the association between parental absence in childhood and depressive symptoms among rural community dwellers in Khanh Hoa Province, Vietnam. Data came from 3000 individuals aged 40–60 years old who participated in the baseline survey of the Khanh Hoa Cardiovascular Study. Depressive symptoms were assessed with the 11-item Center for Epidemiologic Studies Depression Scale. Self-reported information on parental absence due to death, divorce, or outmigration to other locations before the age of 15 was also obtained. A Poisson regression analysis with a robust variance estimator was used to examine associations. Experiencing parental absence at 3 - < 15 years old and before 3 years old was associated with a 1.21 times (95% confidence interval [CI] = 1.02–1.43) and 1.41 times (95% CI = 1.15–1.73) higher prevalence of depressive symptoms, respectively (p trend <0.001). When examining the associations by the different reasons for the parental absence, the strongest association was found for parental absence due to outmigration to other locations. We had no information on who respondents lived with after they experienced parental absence. In addition, self-reported information on childhood experiences was subject to recall bias. In rural Vietnam, parental absence during childhood was associated with a significantly increased prevalence of depressive symptoms in middle adulthood.